2020
DOI: 10.1111/anu.13145
|View full text |Cite
|
Sign up to set email alerts
|

Feeding marbled spinefoot rabbitfish (Siganus rivulatus) juveniles with β‐mannanase enzyme: An effective tool to enhance growth and immunity and induce low salinity tolerance

Abstract: Siganus rivulatus is a herbivorous marine fish and is considered as an important source of food in the Indo-Pacific and the eastern Mediterranean regions (Lam, 1973). Rearing of S. rivulatus is easy to apply; therefore, it is suitable for aquaculture and has an economic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The total phenolic content for PPP was estimated as 520 ± 2.64 mg gallic acid g −1 , whereas flavonoids were estimated as 65.7 ± 3.41 mg catechin equivalents g −1 (Abdel-Razek et al 2019 ). It was reported that inclusion of the polyphenol-rich algae Laurencia obtusa in the red tilapia diet relieved hypoxia stress effects by reducing the levels of serum cortisol and glucose (Salem et al 2021a , b ). Moreover, this improvement in the resistance of Nile tilapia to salinity stress by dietary supplementation of PPP may be due to the presence of pinellic acid and quercetin in PPP, which act as anti-inflammatory agents (Aruwa et al 2019 ; Durazzo et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total phenolic content for PPP was estimated as 520 ± 2.64 mg gallic acid g −1 , whereas flavonoids were estimated as 65.7 ± 3.41 mg catechin equivalents g −1 (Abdel-Razek et al 2019 ). It was reported that inclusion of the polyphenol-rich algae Laurencia obtusa in the red tilapia diet relieved hypoxia stress effects by reducing the levels of serum cortisol and glucose (Salem et al 2021a , b ). Moreover, this improvement in the resistance of Nile tilapia to salinity stress by dietary supplementation of PPP may be due to the presence of pinellic acid and quercetin in PPP, which act as anti-inflammatory agents (Aruwa et al 2019 ; Durazzo et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These fish are characterized by their fast growth, reproduction capacity, physiological strength, potent resistance to stress and diseases, adaptability to different environmental conditions, and trophic plasticity (El-Sayed 2020a ). Despite the fact that tilapia are euryhaline, which can tolerate a wide range of water salinity (El-Sayed 2020b ), they also show a significant increase in Na + , K + -ATPase activity in the gill, plasma osmolality, cortisol, glucose, growth hormone and prolactin after exposure to salinity stress (Fiess et al 2007 ; Breves et al 2010 ; Angadi et al 2021 ; Sallam et al 2020 ). Moreover, the physiological changes associated with salinity acclimation in tilapia are energy-demanding (Morgan et al 1997 ; Angadi et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the GI tract is the primary site for feed digestion and nutrient absorption, its morphology can be used to assess intestinal health, feed consumption ability, and fish growth [56][57][58]. For normal intestinal functions, intestinal morphology must be healthy [59].…”
Section: Discussionmentioning
confidence: 99%